Managing Human Resources for Surge Capacity in Referral Hospitals Based on WHO Hospital Readiness Checklist for Covid-19 - Dinia, Fitri; Trisnantoro, Laksono; Helmi, Mochamat (Folia Medica Indonesiana, 2022)
Highlights: • Managing human resources for surge capacity in three referral hospital at West Kalimantan was evaluated. • Availability, mobilization and recruitment, duties division, and hospital staff welfare are the reasons for referral hospitals in West Kalimantan are not optimal to face surge capacity during the Covid-19 pandemic. • Provincial Health Office role had not been optimal in the HR management at referral hospitals during the Covid-19 pandemic. Abstract: One of the components of effective disaster response management to deal with surge capacity in referral hospitals in West Kalimantan, Indonesia, was to ensure the adequacy of the number of human resources (health workers). This study was conducted to evaluate three referral hospitals and identify the role of the West Kalimantan Provincial Health Office in managing human resources for health workers facing surge capacity due to the Covid-19 pandemic. This study used Rapid Assessment Procedures with qualitative and quantitative methods. Data were collected through observation and interview by using instruments adopted from the Checklist of WHO Hospital Readiness for Covid-19. Based on the checklist, 51.1% of referral hospitals had implemented HR management regarding staff availability. However, the readiness of referral hospitals in West Kalimantan to face surge capacity had not been optimal in several key components, such as staff availability, staff mobilization and recruitment, division of staff duties, and hospital staff welfare during the Covid-19 pandemic. The role of the Provincial Health Office had not been optimal in managing HR at referral hospitals. The Provincial Health Office only played an active role at the beginning of the Covid-19 pandemic, especially for the provision of volunteers. Meanwhile, in the second year of the Covid-19 pandemic, the role of the Provincial Health Office had decreased, especially in the staff availability and training at the referral hospitals. Therefore, the role of the West Kalimantan Provincial Health Office in HR management at the referral hospitals was highly not dominant (17.78%). The central government should regulate the authority of the Provincial Health Office as the leading sector in all types of referral hospitals to integrate all potencies and human resources of local governments to maximize HR management in referral hospitals to face surge capacity due to the increased cases of Covid-19.